Signs of the United Nations SDGs in University Curriculum: The Case of the University of Iceland - Auður Pálsdóttir; Lára Jóhannsdóttir (Sustainability, 2021)
Sustainability is a pressing topic in all universities. Institutions are determining what the implications of such a development are, e.g., on how courses that students are provided with should develop, what to change, what to add, and how these changes could be brought about. The purpose of this research was to provide an overview of the United Nations Sustainable Development Goals (SDGs) in the curriculum of five schools at the University of Iceland and an overview of individual SDGs for the university, to identify the main challenges and opportunities for improvement. Data collection included analysis of every single university’s course description and learning outcomes using a curriculum analysis key designed for the SDGs. Results indicated strong signs of SDG 4 (quality education) at the School of Education and the School of Social Sciences and SDG 3 (good health and well-being) at the School of Health Sciences. For the university, the results revealed a very limited emphasis on four SDGs, i.e., SDG 1 (no poverty), SDG 2 (zero hunger), SDG 6 (clean water and sanitation), and SDG 13 (climate actions). The results can serve as a benchmark for other universities, e.g., for comparison of results and their situation when creating policy and practices that include implementing the SDGs. Additionally, they can be used for comparison within the University of Iceland as a whole or within each school to monitor change.